Consumer experience and perception in gamification marketing: evidence from the user survey of POPMART - Zhang, Jinyu; Zou, Yuyun; Wang, Song; Xiang, Yong (Frontiers in Communication, 2025)
BackgroundBrand loyalty is crucial for brand marketing effectiveness. Typically, companies may struggle with user feedback and advertising impact, making it challenging to establish consumer habits and receive positive feedback. Gamification marketing engages consumers actively in brand advertising as players. However, the underlying mechanisms of gamification and its impact on advertising effectiveness remain unclear, especially in new consumer domains lacking targeted experiences.MethodsBy introducing the USE model that incorporates utilitarian, social, and experiential purposes, we critically elevate the marketing domain’s game evaluation model. Using a survey component of a new online applet, we survey consumers to examine their perceptions and experiences with gamified marketing, exploring data models related to consumer usage motivations and influence levels. The impact of user habits, membership, recommendations, and usage intentions on brand loyalty is analyzed.ResultsOur empirical results demonstrate that gamification marketing can effectively increase consumers’ brand loyalty by satisfying utilitarian, social, and experiential purposes, with utilitarian motives showing the strongest significance.DiscussionThis study contributes to enhancing the consumer perception in gamified marketing design, enabling targeted improvements in the experiential effects of gamified marketing for businesses.